The Relationship Between Religiosity and Forgiveness in Wives Who Experience Domestic Violence (KDRT) - Yuni Putri, Dhia Ghina; Devi Rusli (Causalita, 2024)
This study is based on the phenomenon of domestic violence (KDRT) that occurs in many married couples in Indonesia which is very concerning. Violence in intimate relationships is a serious threat to the health and well-being of women. This quantitative descriptive study applies correlational analysis to explain the relationship between religiosity and forgiveness in wives who experience domestic violence, with 90 wives as research subjects. Forgiveness uses the Transgression-Related Interpersonal Motivation Inventory (TRIM-18) scale and for religiosity uses The Centrality of Religiosity Scale. The scale has been tested for validity and reliability. The results of the study showed that forgiveness is in the high category, namely 33 people (36.7%), and religiosity is in the very high category, namely 78 people (86.7%). There is a positive relationship between religiosity and forgiveness, which shows that if the religiosity variable increases, the forgiveness variable also increases.